Measuring the Water Temperature Changes in Ice Abrasive Water Jet Prototype. (2016) - Jerman, Marko; Orbanić, Henri; Lebar, Andrej; Sabotin, Izidor; Drešar, Pavel; Valentinčič, Joško
Abstract: Ice abrasive water jet (IAWJ) technology is a technology under development with the aim to breach the gap in productivity between the abrasive water jet (AWJ) and water jet (WJ) cutting by using ice particles instead of mineral abrasive. Such technology would be clean and environmentally friendlier in comparison with AWJ, while its cutting efficiency would be better than that of WJ. Due to heavy temperature dependence of the mechanical properties of ice used as an abrasive, it is essential that the temperatures occurring in the system are monitored and controlled. This paper presents the results from temperature measurements of water taken from different parts of the IAWJ prototype, both before and after the orifice, at different temperature and pressure conditions, using different orifice sizes.